Efektivitas Adsorben Kitosan - Natrium Tripolifosfat dalam Menurunkan Konsentrasi Fe dan Mn pada Air Sumur - Emeralda Rieke Wibowo; Firra Rosariawari (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
In general, well water or ground water often contains iron (Fe) and manganese (Mn) ions in it. One of the effective water treatment processes to remove heavy metals is adsorption. Natural adsorbents such as chitosan can be effective adsorbents used to reduce heavy metal concentrations in the environment. One of the weaknesses of chitosan is the strength of the mechanical structure and low stability. Therefore, crosslinking modifications were carried out to improve the mechanical structure and reduce solubility. This study aims to determine the effect of sodium tripolyphosphate on the process of making chitosan shrimp shell-sodium tripolyphosphate adsorbent and to determine the optimum conditions of the variation of the adsorbent and the mass used. The research variables used were the sodium-tripolyphosphate concentration of 0.25%; 0.50%; and 1.00%, the mass of the adsorbent in the column was 5 grams and 7.5 grams, and the sampling times were 20 minutes, 40 minutes, 60 minutes, 80 minutes, 100 minutes, 120 minutes, 140 minutes and 160 minutes. The results showed that the 1% chitosan-sodium tripolyphosphate adsorbent with a mass of 7.5 grams was the most optimal in reducing the content of Fe by 92% and Mn by 93%.